Dari Etika Domestik ke Etika Kekuasaan: Membaca Qiwa>mah dalam QS. al-Nisa>‘/4:34 - Rasyid, Muhammad Dirman; Reskiani, Anugrah; Nur Murdan, Muhammad; Makmur (STAIN Majene, 2025)
This article examines the concept of qiwa>mah in QS. al-Nisa>‘/4:34 by going beyond interpretations that limit it to domestic ethics in husband-wife relationships. Through a qualitative approach based on literature study and semantic-relational analysis, this article shows that qiwa>mah not only functions as a normative status or legitimization of gender hierarchy, but also as an ethical function that arises from certain excess (fadl) and is manifested through concrete responsibility (anfaq). By placing the family as the smallest social unit, QS. al-Nisa>‘/4:34 can be read as a pedagogical medium of the Qur’an to explain the principles of managing asymmetrical relationships ethically. This reading places qiwa>mah as a framework of the ethics of power that emphasizes protection, justice, and the prevention of injustice, and is relevant to broader social and political relations. Artikel ini mengkaji konsep qiwa>mah dalam QS. al-Nisa>‘/4:34 dengan melampaui pembacaan yang membatasinya sebagai etika domestik dalam relasi suami-istri. Melalui pendekatan kualitatif berbasis studi kepustakaan dan analisis semantik-relasional, artikel ini menunjukkan bahwa qiwa>mah tidak hanya berfungsi sebagai status normatif atau legitimasi hierarki gender, melainkan juga sebagai fungsi etis yang lahir dari kelebihan (fadl) tertentu dan diwujudkan melalui tanggung jawab konkret (anfaq). Dengan menempatkan keluarga sebagai unit sosial terkecil, QS. al-Nisa>‘/4:34 dapat dibaca sebagai medium pedagogis Al-Qur’an untuk menjelaskan prinsip pengelolaan relasi asimetris secara etis. Pembacaan ini menempatkan qiwa>mah sebagai kerangka etika kekuasaan yang menekankan perlindungan, keadilan, dan pencegahan kezaliman, serta relevan bagi relasi sosial dan politik yang lebih luas